Bronchiectasis. (May 2016) - Johnson, Chris; Haworth, Charles
Abstract: Bronchiectasis is clinically defined as irreversible airways dilatation associated with chronic inflammation and infection. It is a cause of chronic cough and recurrent lower respiratory tract infections. The prevalence of diagnosed bronchiectasis is probably increasing as a result of an ageing population and the increased use of radiological investigations. The diagnosis is secured by high-resolution computed tomography of the chest, which should prompt referral to a specialist unit to investigate for one of many underlying causes. These can be diagnosed in up to 65% of patients and when made can significantly alter management. The pathogenesis of bronchiectasis is best understood as a vicious cycle of inflammation and infection. Although clinical trial data are often lacking, there are many treatment options that target each of the steps within this cycle. These include the use of airway clearance techniques, mucoactive agents, anti-inflammatories and antibiotics for both exacerbation and prophylaxis. This intensive approach is necessary as there is a considerable associated morbidity, mortality and health economic cost. However, patient adherence to such complex and long-term treatment can be difficult. This article discusses the epidemiology, pathogenesis, diagnosis and management of bronchiectasis.